Nutritional status with biochemical and anthropometric indicators and lifestyles in a Covid -19 pandemic in university students from central Peru - Pilco Villagra , María Del Carmen (2021)
Objectives: To determine the relationship between the nutritional status with biochemical and anthropometric indicators and healthy lifestyles of the students of the IV semester - Obstetrics of Roosevelt University. Huancayo. Material and Methods: The non-experimental study with a correlational quantitative approach, the SPSS version 23 Windows was used. Results: 3.4% of the students have moderate anemia, 27.60% mild anemia, 69% normal values. Regarding the variable diet, 34.5% poor diet, 58.6% regular diet and 6.9% with good diet in the COVID-19 pandemic. Variable IMC: 75.9% with normal diagnosis, 14.2% overweight, 3.4% obese and 3.4 thin. Conclusion: According to Spearman's Rho, the results obtained Rho = 0.582; p = 0.000 less than 0.05; there is a moderate correlation with a considerable relationship between biochemical indicators (hemoglobin levels) and COVID-19 pandemic lifestyles (diet); consequently the null hypothesis (Ho) is rejected. Regarding anthropometric indicators (BMI) and lifestyles (food) COVID-19 pandemic; a correlation coefficient of 0.602 was obtained; then there is a good correlation between both variables.